PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RESTORAN WHIZ PRIME HOTEL MALANG - Riani Prihatini Ishak; Siti Nur Azizah (Bogor Hospitality Journal, 2022)
In the conditions of the COVID-19 pandemic, the hotel industry was also affected and many things were done by the hotel to retain hotel visitors, one of which was to improve the quality of service so that guests feel satisfied even in the conditions of the COVID-19 pandemic. This study aims to determine how much influence the quality has. service to customer satisfaction. The research method used by the author is a quantitative descriptive research method with a simple linear regression analysis technique. The sample in this study amounted to 87 respondents. The sampling method used by the author is using probability sampling. Collecting data using a questionnaire. Questionnaires were given to guests who visited the Whiz Prime Hotel Malang Restaurant. Judging from the coefficient table obtained a significance value of 0.000 <0.05, so it can be concluded that the Service Quality variable (X) has an effect on the Customer Satisfaction variable (Y). The results of this study indicate that the regression equation = 40.140 + 0.270X for every additional 1 unit of service quality value, the value of customer satisfaction increases by 0.270. The regression coefficient is positive, so it can be said that the direction of the influence of the X variable on Y is positive and it is known that the tcount is 4.850 > ttable 1.988, so it can be concluded that the Service Quality variable (X) has an effect on the Customer Satisfaction variable (Y). Ha accepted.